2012
DOI: 10.1016/j.jcis.2012.06.051
|View full text |Cite
|
Sign up to set email alerts
|

Thickness, stability and contact angle of liquid films on and inside nanofibres, nanotubes and nanochannels

Abstract: While the stability of liquid films on substrates is a classical topic of colloidal science, the availability of nanostructured materials, such as nanotubes, nanofibres and nanochannels, has raised the question of how the stability of liquid films and their wetting behaviour is affected by nanoscale confinement. This paper will present the conditions for the stability of liquid films on and inside cylindrical solid substrates with nanometre scale characteristic dimensions. It is shown that the stability is det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 24 publications
2
25
0
Order By: Relevance
“…According to the thermodynamic equilibrium principle and G–M binary gas isothermal adsorption model, when the water film and gas reach an equilibrium, the separation pressure is related to the relative vapor pressure as follows:h=-italicRTVwlnpp0where V w is the molar volume of water, the universal gas constant is R = 8.314 J/(mol K), and T is the Kelvin temperature.…”
Section: Characteristics Of the Water Film And Microscopic Surface Fomentioning
confidence: 99%
See 1 more Smart Citation
“…According to the thermodynamic equilibrium principle and G–M binary gas isothermal adsorption model, when the water film and gas reach an equilibrium, the separation pressure is related to the relative vapor pressure as follows:h=-italicRTVwlnpp0where V w is the molar volume of water, the universal gas constant is R = 8.314 J/(mol K), and T is the Kelvin temperature.…”
Section: Characteristics Of the Water Film And Microscopic Surface Fomentioning
confidence: 99%
“…For tight porous media, the Knudsen diffusion cannot be ignored, and Darcy's law is not valid; consequently, conventional fluid flow simulation methods are no longer applicable. Several scholars have performed experiments considering natural or artificially bonded porous media and demonstrated that the particle size and porosity have a significant effect on the fluid flow. However, experimental methods are rather time‐consuming and expensive.…”
Section: Introductionmentioning
confidence: 99%
“…The difference of pressure between the thin film and the bulk phase is given by: pfpw=Π(h) where Π ( h ) is the disjoining pressure, MPa, which is the sum of a molecular force, an electrostatic force and a structural force . For completely wetting cases, the molecular force dominates the other components, and thus the molecular component is only considered in this work. For water film retention on a flat surface, the disjoining pressure is given by: normalΠflat(h)=Agws6πh3 …”
Section: Water Retention Characteristicsmentioning
confidence: 99%
“…For water film retention inside a cylindrical surface, the disjoining pressure is given by normalΠcircle(h)=Agws6πh3LL2h where A gws is the Hamaker constant for gas–water–solid interaction, J.…”
Section: Water Retention Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation